Enhancing Nahwu Learning Effectiveness Through Pantun-Based Pedagogical Media - Uswatun Khasanah; Kristina Imron; Kemas Muhammad; Mikdar Rusdi; Keysha Aurellia Az-Zahra; Muhammad Fadlul Amal (Journal of Arabic Language Teaching, 2025)
Nahwu learning is a crucial aspect of mastering Arabic but is often seen as difficult and monotonous. This study examines the effectiveness of using pantun, a traditional Indonesian poetic form, as a medium to enhance Nahwu learning. A mixed-method approach was used, combining quantitative and qualitative data through observation, interviews, documentation, and pretest-posttest assessments. The analysis included validity, normality, Wilcoxon, homogeneity, and N-Gain tests. The results showed a significant improvement in students' scores, with pretest averages of 66.42 rising to 92.38 on the posttest. Statistical analysis using SPSS revealed that the data were not normally distributed, which led to the use of the Wilcoxon signed-rank test. The test results (p = 0.000 < 0.05) indicate a significant improvement in learning outcomes. The homogeneity test result (p = 0.341 > 0.05) confirmed consistent data characteristics, and the N-Gain analysis showed a high average score of 78.92, categorized as effective. Qualitative data supported this, showing increased student motivation and engagement when pantun was used. This study proves that pantun is an effective teaching medium and contributes to culturally responsive pedagogy in Arabic education. It fills a research gap by demonstrating how local cultural media can enhance traditional grammar instruction.